Global reorganization of atmospheric circulation during Dansgaard-Oeschger cycles - Fohlmeister, Jens; Sekhon, Natasha; Columbu, Andrea; Vettoretti, Guido; Weitzel, Nils; Rehfeld, Kira; Veiga-Pires, Cristina; Ben-Yami, Maya; Marwan, Norbert; Boers, Niklas (Proceedings of the National Academy of Sciences of the United States of America, 2023)
Ice core records from Greenland provide evidence for multiple abrupt cold-warm-cold events recurring at millennial time scales during the last glacial interval. Although climate variations resembling Dansgaard-Oeschger (DO) oscillations have been identified in climate archives across the globe, our understanding of the climate and ecosystem impacts of the Greenland warming events in lower latitudes remains incomplete. Here, we investigate the influence of DO-cold-to-warm transitions on the global atmospheric circulation pattern. We comprehensively analyze δ18O changes during DO transitions in a globally distributed dataset of speleothems and set those in context with simulations of a comprehensive high-resolution climate model featuring internal millennial-scale variations of similar magnitude. Across the globe, speleothem δ18O signals and model results indicate consistent large-scale changes in precipitation amount, moisture source, or seasonality of precipitation associated with the DO transitions, in agreement with northward shifts of the Hadley circulation. Furthermore, we identify a decreasing trend in the amplitude of DO transitions with increasing distances from the North Atlantic region. This provides quantitative observational evidence for previous suggestions of the North Atlantic region being the focal point for these archetypes of past abrupt climate changes.